Experiments in organizational economics - Goerg, Sebastian J., 1980-; Hamman, John R. (Emerald, 2017)
Research in Experimental Economics (REXE) Volume 19 entitled 'Experiments in Organizational Economics' highlights the importance of replicating previous economic experiments.
Keywords: Organizational behavior -- Economic aspects.; Economics, Mathematical.; Experimental economics.; elektronické knihy; electronic books